Appraisal of Comprehensive Scheme of Increasing Tax Base Proposed by FPCCI - Malik, Muhammad Bilal (Journal of Public Policy Practitioners, 2022)
Pakistan’s pace of development has been hindered due to a huge informal economy and a narrow tax-base scheme. Sequential successive governments have been unable to remove the formidable impediments due to multifarious factors like cultural mindset, flawed policies, organizational constraints, and rampant corruption. A large segment of the economy is not contributing its fair share into the national revenue collection mainly/primarily due to a lack of ownership by the masses in general and businesses in particular. Sequential successive governments have failed to allay their apprehensions relating to the tax-based system, thereby winning extensive cooperation of FBR’s potential to collect taxes, which has been severely compromised because of its non-inclusive approach. This paper aims to critically examine the political legitimacy, operational feasibility, and financial sustainability of the proposals for the Broadening of Tax Base (BTB) scheme proposed by the Federation of Pakistan Chambers of Commerce and Industry (FPCCI).